(untitled) (Islas, 2024)
Introduction: The loss of female power in the Osha-Ifá religious complex entails discrepancies that demand analysis. This study aims to argue the contradictions of female exclusion in the Osha-Ifá religious complex. Methods: Bibliographic analysis, content analysis, non-participant open included observation, non-participant covert included observation, semi-structured interview, life history, and conversational analysis were applied to an intentional sample of 239 subjects. Results: The contradictions are argued through historical foundations of the origin and development of this religion, social and cultural conditioning, and from the dissociation of the myth-symbolic-ritual triad in the sexual division of labor, femininity in religiosity, participation, and autonomy within the Osha-Ifá religious complex. Conclusions: These contradictions are rooted in a patriarchal system-field that denies, devalues, or forgets the origin, survival, and preeminence of the Osha-Ifá religious complex associated with female religious leadership and empowerment.